Ketone monoester ingestion alters metabolism and simulated rugby performance in professional players - Peacock, O. J.; Gonzalez, J. T.; Roberts, S. P.; Smith, A.; Drawer, S.; Stokes, K. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Ketone ingestion can alter metabolism but effects on exercise performance are unclear, particularly with regard to the impact on intermittent-intensity exercise and team-sport performance. Nine professional male rugby union players each completed two trials in a double-blind, randomized, crossover design. Participants ingested either 90 ± 9 g carbohydrate (CHO; 9% solution) or an energy matched solution containing 20 ± 2 g CHO (3% solution) and 590 mg/kg body mass ß-hydroxybutyrate monoester (CHO + BHB-ME) before and during a simulated rugby union-specific match-play protocol, including repeated high-intensity, sprint and power-based performance tests. Mean time to complete the sustained high-intensity performance tests was reduced by 0.33 ± 0.41 s (2.1%) with CHO + BHB-ME (15.53 ± 0.52 s) compared with CHO (15.86 ± 0.80 s) placebo (p = .04). Mean time to complete the sprint and power-based performance tests were not different between trials. CHO + BHB-ME resulted in blood BHB concentrations that remained >2 mmol/L during exercise (p < .001). Serum lactate and glycerol concentrations were lower after CHO + BHB-ME than CHO (p < .05). Coingestion of a BHB-ME with CHO can alter fuel metabolism (attenuate circulating lactate and glycerol concentrations) and may improve high-intensity running performance during a simulated rugby match-play protocol, without improving shorter duration sprint and power-based efforts.